Prevalensi Hipertensi dan Diabetes Mellitus Tipe-2 di Puskesmas Kota Manado Tahun 2015 - Palandeng, Henry M.F. (UNIVERSITAS SAM RATULANGI, 2015)
Diabetes mellitus and hypertension are interrelated diseases that affect an individual becomes atherosclerotic disease. The prevalence of hypertension and diabetes increased in industrialized countries because of the aging population. The aim of this study was to determine the prevalence of diabetes mellitus and hypertension in Manado City Community Health Center. This study uses a descriptive study with cross sectional (cross-sectional) with secondary data taken in patients in three community health centers in Manado (Sario, Karombasan and Teling). Results showed the prevalence of type 2 diabetes mellitus patients mostly at age> 60 years were 71 patients and more men - men with a number of 17 people (59%). For Hypertension with female sex more amounted to 545 people (58%) and in the age group> 60 years.